Proteomics Analysis of CA1 Region of the Hippocampus in Pre-, Progression and Pathological Stages in a Mouse Model of the Alzheimer’s Disease - Gurel, Busra; Cansev, Mehmet; Koc, Cansu; Ocalan, Busra; Cakir, Aysen; Aydin, Sami; Kahveci, Nevzat; Ulus, Ismail H.; Sahin, Betul; Basar, Merve Karayel; Baykal, Ahmet Tarik (Current Alzheimer Research, 2019)
Background: CA1 subregion of the hippocampal formation is one of the primarily affected structures in AD, yet not much is known about proteome alterations in the extracellular milieu of this region. Objective: In this study, we aimed to identify the protein expression alterations throughout the pre-pathological, progression and pathological stages of AD mouse model. Methods: The CA1 region perfusates were collected by in-vivo intracerebral push-pull perfusion from transgenic 5XFAD mice and their non-transgenic littermates at 3, 6 and 12 wereβmonths of age. Morris water maze test and immunohistochemistry staining of A performed to determine the stages of the disease in this mouse model. The protein expression differences were analyzed by label-free shotgun proteomics analysis. Results: A total of 251, 213 and 238 proteins were identified in samples obtained from CA1 regions of mice at 3, 6 and 12 months of age, respectively. Of these, 68, 41 and 33 proteins showed statistical significance. Pathway analysis based on the unique and common proteins within the groups revealed that several pathways are dysregulated during different stages of AD. The alterations in glucose and lipid metabolisms respectively in pre-pathologic and progression stages of the disease, lead to imbalances in ROS production via diminished SOD level and impairment of neuronal integrity. Conclusion: We conclude that CA1 region-specific proteomic analysis of hippocampal degeneration may be useful in identifying the earliest as well as progressional changes that are associated with Alzheimer’s disease.
Keywords: 5XFAD